An Eco-Friendly Method to Synthesize Potent Antimicrobial Tricyclic Flavonoids - Loredana-Elena Mantea; Cristina-Veronica Moldovan; Mihaela Savu; Laura Gabriela Sarbu; Marius Stefan; Mihail Lucian Birsa (MDPI AG, 2024)
The rapid emergence and spread of multidrug-resistant microorganisms is threatening our ability to treat common infections, with serious medical, social, and economic consequences. Despite substantial progress in the global fight against antibiotic resistance, the number of effective antibiotics is rapidly decreasing, underlying the urgent need to develop novel antimicrobials. In the present study, the green synthesis of novel iodine-substituted tricyclic flavonoids has been accomplished using an eco-friendly reagent, HPW-SiO2, as a cyclization agent for the precursor 3-dithiocarmamic flavanones. In vitro antimicrobial activity of the new compounds was evaluated using minimum inhibitory concentration (MIC) and minimum bactericidal/fungicidal concentrations. All tested compounds displayed potent inhibitory activity against all tested microbial strains, with the lowest MIC values of 0.12 µg/mL and 0.48 µg/mL recorded for compound 5c against Gram-positive bacteria Bacillus subtilis and Staphylococcus aureus. Higher MIC values (7.81 µg/mL) were registered for several flavonoids against Gram-negative bacteria Escherichia coli and Acinetobacter pittii. No inhibitory activity was evidenced against Pseudomonas aeruginosa strain. The highest antifungal activity was displayed by flavonoid 5d against Candida krusei (MIC = 3.9 µg/mL). The same compound also exhibited the most potent bactericidal and fungicidal activity against Bacillus subtilis (0.9 µg/mL) and Staphylococcus aureus (1.97 µg/mL), Candida albicans, and Candida krusei (7.81 µg/mL). Based on the reported results, we believe that the novel iodine-substituted tricyclic flavonoids have good potential to become new antimicrobial agents effective against bacterial and fungal strains, including WHO-priority pathogens.